Power Flow Study of Untransposed Transmission Lines - Pulungan, Ali Basrah; Hadi, Sasongko Pramono; Soedjatmiko, Soedjatmiko (2007)
This paper investigates the unbalanced three-phase power flow, mainly to know the voltage magnitude, current and power each bus and lines. Unbalanced three-phase system can be caused untransposed lines, unbalanced loads or both of them. In this case, unbalanced of three-phase system is done with making simulation in 14 bus system from IEEE : untransposed lines of balanced loads. This simulation is done with using EDSA software to do phase dependent power flow analysis. The result of unbalanced three-phase power flow simulation caused untransposed lines of balanced loads is showing the difference among voltage magnitude, current and power in each phase. The greatest unbalanced bus voltage percentage is 2.38%. The total percentage each current a, b and c in untransposed lines of balanced loads are 30.94%, 33.06%, 36.00%. The total percentage each active power a, b and c are 31.26%, 29.31% and 39.43% and the total percentage each reactive power a, b and c are 35.18%, 41.34% and 23.48%